Ultrasound guided FNA of thyroid performed by cytopathologists enhances Bethesda diagnostic value. Issue 10 (26th July 2016) - Wu, Maoxin; Choi, YoonSun; Zhang, Zesong; Si, Quisheng; Salem, Fadi; Szporn, Arnold; Zhang, David; Burstein, David; Teng, Marita; Miles, Brett A.; Genden, Eric
Abstract : Background: Ultrasound (US) guided fine needle aspiration (FNA) biopsy of thyroid are examined and reported by cytopathologists based usually on The Bethesda System for Reporting Thyroid Cytopathology (BTC) regardless of the procedure's performers. This study is designed to determine whether there is any performer‐dependent difference. Methods: Six hundred and fifty‐one thyroid US‐FNAs in correlation with surgical follow‐up (SFU) were studied. The statistical analysis was performed using the surgical pathology diagnosis as the gold standard. Results: Among the 283 cases performed by cytopathologists, there were 8 (2.8%) nondiagnostic (BTC I), 197 (69.6%) benign (BTC II), 31 (11%) atypical (BTC III), 14 (5%) suspicious for follicular neoplasm (BTC IV), 12 (4.2%) suspicious for malignancy (BTC V), and 21 (7.4%) positive for malignancy (BTC VI), and there were 55 (19.4%) cases with SFU. The 368 cases performed by others showed 76 (21%) BTC I, 238 (65%) BTC II, 26 (7%) BTC III, 10 (3%) BTC IV, 9 (2.5%) BTC V 5, and 9 (2.5%) BTC VI, and there were 26 (7%) cases with SFU. The cytopathologist group achieved better sensitivity (91.3 vs.78%); slightly better specificity (83.3 vs. 82%); better positive predictive value (87.5 vs. 70%); similar negative predictive value (88.2 vs. 88%); and better overall accuracy (87.8 vs. 81%) compared with the non‐cytopathologist group. Overall the difference for all statistical values is significant different (P = 0.041). Conclusion: US‐FNA performed by cytopathologists showed a lower unsatisfactory rate and significantly better overall statistical values. Cytopathologists may play an important role in thyroid patient care. Diagn. Cytopathol. 2016;44:787–791. © 2016 Wiley Periodicals, Inc.